Interreligious theology: its value and mooring in modern Jewish philosophy - Meʾir, Efrayim (De Gruyter, 2015)
This book is the first greater attempt to construct a dialogical theology from a Jewish point of view. It contributes to an emerging new theology that promotes the interrelatedness of religions in which encounter, openness, and permanent learning are central. Meir analyses and critically discusses the writings of great contemporary Jewish dialogical thinkers and argues that the values of interreligious theology are moored in their thoughts